Agency development of high school students in the process of professional self-determination - Evgeniya S. Volkova; Alexander V. Kaptsov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
An urgent problem in educational psychology is the effectiveness of students’ professional self-determination. At the same time, for successful self-determination it is necessary to possess the qualities of a full-fledged agent. Scientists, despite differences in the definitions of the concepts “agent” and “agency”, agree on general characteristics: the agent must have independence (autonomy), activity, responsibility, the ability for self-reflection and self-knowledge. All these are necessary qualities for high school students to make a conscious choice of their future profession. Accordingly, the development of student agency becomes particularly important in education. At the same time, students’ value orientations act as one of the components of the subject’s activity, as well as a factor in successful self-determination. The aim of this study was to determine the characteristics of the agency development of high school students in the process of professional development. The study involved two samples of students (eleventh and ninth grades of a secondary school). Ninth grade students were divided into an experimental group, which received professional self-determination training, and a control group, which received training as usual. Diagnostic sections in the ninth grade took place in three stages: before the training, immediately after the training (19 weeks later) and on the same sample in the 10th grade (7 months after the second section). The questionnaire of the stages of agency development of high school students (OSS-SH) and the projective method of assessing the states of the stages of agency development of students were used as diagnostic methods. Mathematical processing of the obtained data was carried out by using the Wilcoxon T-test to compare changes in parameters over time, and the non-parametric tau-Kendall correlation coefficient to identify relationships. As a result of the study, features of the agency development of high school students in the process of professional self-determination were identified, including the integrity of the stages, the influence of career guidance activities, in this case training, on changes in the states of the stages of agency as well as the relationship between the agency development and the value of the stage for the student and understanding of the necessary steps to achieve the ideal stage level. The practical significance of this study is in substantiating the need for career guidance training for high school students in order to increase educational motivation, independence and the quality of the work they perform.